2008
DOI: 10.3368/le.85.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Objective or Multi-Objective? Two Historically Competing Visions for Benefit-Cost Analysis

Abstract: As they embraced benefit-cost analysis during the mid twentieth century, economists faced several challenges. One challenge was to reconcile two visions for the place of the economist in policy analysis, one limited to providing positive analysis for decisionmakers, the other allowing normative judgments. This tension came to a crisis when, in the 1960s, the Water Resources Council introduced multi-objective benefitcost analysis. The surrounding debate highlights the way philosophical differences can drive the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…Jardini's narrative thus suggests that a major channel whereby social unrest and economic and political disturbances may have weighted on economic research was through governments' responses, political and legal. A detailed case study of such process is provided by Banzhaf's (2009) account of how Cost-Benefit Analysis was used for water resources 19 management. He shows that competing ways of using cost-benefits tools for water resources management rested upon diverging conceptions of welfare and of the economist' role in the policy-making process.…”
Section: Economists Social Ills and Public Policiesmentioning
confidence: 99%
“…Jardini's narrative thus suggests that a major channel whereby social unrest and economic and political disturbances may have weighted on economic research was through governments' responses, political and legal. A detailed case study of such process is provided by Banzhaf's (2009) account of how Cost-Benefit Analysis was used for water resources 19 management. He shows that competing ways of using cost-benefits tools for water resources management rested upon diverging conceptions of welfare and of the economist' role in the policy-making process.…”
Section: Economists Social Ills and Public Policiesmentioning
confidence: 99%
“…Therefore, it has been suggested that successful fisheries management is largely a question about transparency and congruency of objectives (Dankel et al, 2008;Hilborn, 2007;Squires, 2009). In principle, there are two potential ways to give policy recommendations when facing multiple objectives; see Banzhaf (2009). The first approach assumes that the relative shadow prices of financial, environmental and social objectives are known so that their weighted sum can be maximized.…”
Section: Introductionmentioning
confidence: 99%
“…It was, ultimately, the political process that should decide on the weighting: "in no event should the technician arrogate the weighting of objectives to himself," Eckstein (1961, p. 449) argued. The former group thus emphasized consumer sovereignty, while the latter promoted a vision of political sovereignty in which elected officials represented the collective choice of citizens (Banzhaf 2009). Similar debates took place in urban economics, which explained why MIT welfare economist Jerome Rothenberg (1967, p. 21-22) tried to revamp the CBA techniques used to evaluate urban renewal policies as the reflection of a democratic decision process.…”
Section: Government Choices Reflecting Citizens' Choices? the Difficumentioning
confidence: 99%